Strategi Branding Organisasi PSHT Ranting Gondang dalam Membangun Citra Positif di Masyarakat untuk Meningkatkan Kepercayaan dan Partisipasi Aktif Anggota - Hanifah Puspita Dewi; Rakhmad Saiful Ramadhani; Moch. Ichdah Asyarin Hayau Lailin (Lembaga Pengembangan Kinerja Dosen, 2025)
Culture in Indonesia is not just a story in the past, but an effort to understand how to know aspects of life. Such as values, beliefs, arts, morals, customs, science, technology, and ways of life that have evolved or influenced each other in history, then One of them is through the traditional martial arts culture of pencak silat is a martial art originating from Indonesia, not only martial arts but a rich and multidimensional cultural heritage that has close ties in the culture of society. Pencak silat Persaudaraan Setia Hati Terate (PSHT) is the largest pencak silat organization in Indonesia which has the goal of forming noble people, knowing right from wrong, and being pious to God Almighty. PSHT is PSHT is one of the pencak silat founded by Ki Hajar Harjo Oetomo in Madiun City, East Java in 1922. This study uses a qualitative research type with a qualitative descriptive approach. It aims to understand in depth the branding strategy of PSHT Ranting Gondang in building a positive image in the community and member solidarity, with Data Collection techniques: In-depth interviews, participatory observation, document analysis. The results of the research on the Branding Strategy of PSHT Gondang Branch in Building a Positive Image in the community can be understood in its active role in educating, directing members in a positive direction, and not only its role, PSHT has a primary function in the community in changing the image into a long-term reputation for the future of PSHT Gondang Branch. The community also contributed a lot of energy and thought to confirm that the branding strategy implemented by PSHT Gondang Branch has effectively integrated various elements (noble values and ethics, internal cultural values, vision and mission, real social behavior and actions.